(3GdaNQjs - (3Rjf GdOjf CHh eMeO Hf GdMSf GdMGSH GdcQNjs
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI Efj hLOJ GdMSGH ehVhYkG dGNQGL GdeMehdGJ ef GdeYdheGJ aj LejY GfhGYg s
(3BNQgG (B:s
(3GMJLJ Cf JYJe GKfjf hKdGKjf ecYHkG Ydi ecYHjf MJj jNQL SJI YTQ GMOkG HYOd ecYHjf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs